1981
DOI: 10.1149/1.2127194
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Electrodeposition of Zinc Alloys Containing a Small Amount of Cobalt

Abstract: Corrosion resistant Zn‐Co alloys were electrodeposited on the steel sheet cathode from an acid galvanizing bath containing a small amount of cobalt sulfate. Under most of the plating conditions studied, the anomalous codeposition and, hence, the preferential deposition of electrochemically less noble Zn occurred. The electrodeposition process of the alloy including the Zn hydroxide formation resulting from the rise in pH in the vicinity of the cathode was estimated by electrochemical and spectroscopic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(53 citation statements)
references
References 9 publications
1
52
0
Order By: Relevance
“…Yu et al [19] investigated the temperature dependence of the electrocrystallization of zinc onto a glassy carbon (GC) electrode using cyclic voltammetry and chronoamperometry measurements and found that increasing the temperature increased the nucleation density and modified the nucleation mechanism of zinc electrodeposits. Higashi et al [20] has developed zinc hydroxide layer suppression mechanisms for zinc deposition in acid sulfate baths, which has been confirmed by other authors [21,22]. Sonneveld et al [23] reported that zinc nucleation from a zincate solution on carbon substrate can be interpreted by a model involving instantaneous nucleation in conjunction with three-dimensional hemispherical growth.…”
Section: Introductionmentioning
confidence: 70%
“…Yu et al [19] investigated the temperature dependence of the electrocrystallization of zinc onto a glassy carbon (GC) electrode using cyclic voltammetry and chronoamperometry measurements and found that increasing the temperature increased the nucleation density and modified the nucleation mechanism of zinc electrodeposits. Higashi et al [20] has developed zinc hydroxide layer suppression mechanisms for zinc deposition in acid sulfate baths, which has been confirmed by other authors [21,22]. Sonneveld et al [23] reported that zinc nucleation from a zincate solution on carbon substrate can be interpreted by a model involving instantaneous nucleation in conjunction with three-dimensional hemispherical growth.…”
Section: Introductionmentioning
confidence: 70%
“…The most likely one appears to be "the hydroxide suppression mechanism" [25][26][27][28]. According to this concept, coevolution of hydrogen during the deposition causes an increase of pH at the electrode/solution interface, producing hydrolysis of less noble metal species and their precipitation as a layer of solid hydroxide.…”
Section: Anomalous Codepositionmentioning
confidence: 99%
“…consumption [26,53,55]. The formation of zinc hydroxide or some dehydration product, such as ZnO, it is hard to imagine here, since there would need to be a strong alkalization at the electrode surface to reach a pH of 5.1 at which insoluble Zn(OH) 2 precipitates [35]. Fabri Miranda et al [36] did not observe a sufficient rise in pH for Zn(OH) 2 precipitation at the beginning of ZnNi electrodeposition at pH 1.5 or 3.…”
Section: The Electrodeposition Of Znmentioning
confidence: 99%
“…Alloying of Zn with small quantities of Co increases its corrosion resistance [33]. ZnCo electrodeposition is known to be anomalous, in that the less noble element, Zn, is deposited in preference to the nobler one, Co. Several hypotheses have been proposed to account for anomalous electrodeposition [34][35][36][37][38][39][40][41][42][43][44]. In some cases, suspended ceramic particles are known to interfere with anomalous electrodeposition [5,45,46].…”
Section: Introductionmentioning
confidence: 99%